An Analysis of Students’ Difficulties on Reading Text in Finding Main Idea at the Tenth Graders of SMK Darul A’mal Metro - Harya, Trisna Dinillah (Bulletin of Science Education, 2023)
Reading is about looking through the text for details. The context of this research is explained about the students’ difficulties on reading text in finding main idea. The objective of this research is to know the difficulties that faced by the students in reading text, the factors of the students’ difficulties in finding the main idea in text, the students overcome the difficulties in finding main idea in the text at the tenth graders of SMK Darul A’mal Metro. The research design of this research was qualitative research. The data collecting technique of this research was documentation, observation, and interview. The sample of this research was ten students of Computer and Network Engineering in e class at SMK Darul A’mal Metro. The result of this research shows that the students’ difficulties in reading text at the tenth graders of SMK Darul A’mal Metro is the students still difficult to find the main idea in English text. The factors that caused the students difficult to find the main idea in text are students need a long time in answering question of main idea question, students do not focus while answering question, and students also do not know the meaning of the sentence. Also most of students at the tenth graders of SMK Darul A’mal Metro are do not know what is main idea, and the students do not know how to find the main idea in the text. Another reason of the factor that make the students difficult to find the main idea in English text because of the long sentence, limit vocabulary of students, and the students’ lack of reading strategy. The students’ solving of the difficulties in finding main idea in the text are read again the text, ask the teacher, and ask friends for a help. Keywords: Students’ Difficulties Reading, Finding Main Idea, Reading Text